Citizens and the Crisis Experiences, Perceptions, and Responses to the Great Recession in Europe (Palgrave Studies in European Political Sociology, 2018)
This volume presents evidence-based research on citizens' experiences and reactions to the Great Recession in Europe. How did European citizen experience and react to the crisis? How are the experiences of crisis and political responses socially differentiated? Are some social classes and more deprived groups particularly hard hit? How did the crisis impact on political choices? What types of political action did citizens engage in and why? What were the drivers of populist attitudes and protest participation? This country-based book explores these important dynamics as expressed in diverse national contexts, namely France, Germany, Greece, Italy, Poland, Spain, Sweden, Switzerland, and UK. Each chapter focuses on one of these countries and employs data from the same survey fielded in 2015. This volume is of particular relevance for scholars, students, and practitioners interested in political sociology, comparative politics and European politics. .